Detection of Mycobacterium marinumin in clinically asymptomatic Siamese fighting fish (Betta splendens) from ornamental fish shops in Chiang Mai Province, Thailand - Anucha Sirimalaisuwan (2018)
© 2017 by the Asian Pacific Journal of Tropical Disease. All rights reserved. Objective: To detect Mycobacterium marinum (M. marinum) infections in healthy Siamese fighting fish from ornamental fish shops in Chiang Mai, Thailand. Methods: Mycobacterium spp. were isolated from 380 internal organs of healthy Siamese fighting fish using Löwenstein-Jensen and Middlebrook 7H10 culture media. A 924-bp DNA fragment from mycobacterial 16S rRNA was amplified and digested with BanI and ApaI restriction enzymes to yield unique restriction patterns for each mycobacterial specie. Results: Thirty-five mycobacterial isolates (8.42%) were recovered from 380 Siamese fighting fish; 21 isolates (5.5%) and 11 isolates (2.29%) were identified as M. marinum and Mycobacterium chelonae, respectively. Conclusions: The results demonstrated the presence of M. marinum zoonotic bacterial pathogens in healthy Siamese fighting fish, and underlined the infection risk to humans of not only exposure to infected fish, but also when they manipulate clinically asymptomatic fish.